2016
DOI: 10.1039/c5ta08038j
|View full text |Cite
|
Sign up to set email alerts
|

One-step electrochemical synthesis of tunable nitrogen-doped graphene

Abstract: Nitrogen-doped graphene is synthesized by one-step electrochemical exfoliation of graphite, which exhibits superior catalytic performances towards the oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 54 publications
7
43
0
Order By: Relevance
“…All measured potentials were converted to potential versus reversible hydrogen electrode (RHE) according to the following equation, unless specifiedEvs RHE=Evs Ag/AgCl+E Ag/AgCl+0.059 pHwhere E vs RHE is the potential versus RHE, E vs Ag/AgCl is the potential versus Ag/AgCl and E øAg/AgCl is the potential of Ag/AgCl electrode respect to the standard hydrogen electrode. The Koutechy–Levich (K–L) equation was used to calculate the electron transfer number ( n ) per oxygen molecule in ORR process at the electrodeB=0.2nFC0D02/3v1/61/J=1/JnormalL+1/JnormalK=1/(Bω1/2)+1/JnormalKwhere J is the measured current density, J L is the diffusion limiting current density, J K is the kinetic limiting current density, ω is the rotating speed in rpm, F is the Faraday constant (96 485 C mol −1 ), D 0 is the diffusion coefficient of oxygen in 0.1 mol L −1 KOH (1.9 × 10 −5 cm 2 s −1 ), v is the kinetic viscosity (0.01 cm 2 s −1 ), and C 0 is the buck concentration of oxygen (1.2 × 10 −3 mol L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…All measured potentials were converted to potential versus reversible hydrogen electrode (RHE) according to the following equation, unless specifiedEvs RHE=Evs Ag/AgCl+E Ag/AgCl+0.059 pHwhere E vs RHE is the potential versus RHE, E vs Ag/AgCl is the potential versus Ag/AgCl and E øAg/AgCl is the potential of Ag/AgCl electrode respect to the standard hydrogen electrode. The Koutechy–Levich (K–L) equation was used to calculate the electron transfer number ( n ) per oxygen molecule in ORR process at the electrodeB=0.2nFC0D02/3v1/61/J=1/JnormalL+1/JnormalK=1/(Bω1/2)+1/JnormalKwhere J is the measured current density, J L is the diffusion limiting current density, J K is the kinetic limiting current density, ω is the rotating speed in rpm, F is the Faraday constant (96 485 C mol −1 ), D 0 is the diffusion coefficient of oxygen in 0.1 mol L −1 KOH (1.9 × 10 −5 cm 2 s −1 ), v is the kinetic viscosity (0.01 cm 2 s −1 ), and C 0 is the buck concentration of oxygen (1.2 × 10 −3 mol L −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Electrochemical exfoliation (EE) is one of the important methods to synthesize functionalized graphene as it offers precise control over the degree of functionalization in addition to room temperature operation to ensue morphological invariance. For instance, Bruna et al synthesized graphene oxyfluoride by using electrochemical exfoliation of graphite in an aqueous solution of HF acid.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectroscopy was a very powerful tool for the detection of carbon based groups. Compared with pristine CC and Ar‐CC, the fourier transform infrared spectrum (FTIR) of OM‐CC showed an additional absorption around 1600 and 1800 cm −1 , which was associated with the vibration of COOH and C=O groups (Figure C) . It confirmed that oxygen functionalized sites was formed on the surface of carbon cloth with microwave treatment in air.…”
Section: Resultsmentioning
confidence: 82%